EFFECT OF DIFFERENT LEONARDITE DOSES AND CROSS-SOWING METHODS ON THE GROWTH AND YIELD OF RED LENTIL - Betül KOLAY; Ali Rıza ÖZTÜRKMEN (Journal of Applied Life Sciences and Environment)
This study was carried out to determine the effect of different cross-sowing methods and different doses of leonardite on the growth of red lentils under rain-fed conditions. Treatments consisted of different cross-sowing methods (control, 45° cross-sowing and 90° cross-sowing) and different leonardite doses (0, 500, 1000, 1500, 2000 and 2500 kg ha−1). The trial was carried out in Diyarbakır province in Türkiye. The same rate of leonardite was applied to the same plots for two consecutive years to observe the two-year effect of leonardite in the experiment, which was established with four replications according to the factorial experimental design in the 2018-2019 and 2019-2020 production seasons. A positive effect of leonardite application was observed on the number of nodules and fresh root weight in the first production season. The highest nodule number (11.84) was obtained with 2500 kg ha−1, and the highest fresh root weight (0.24, 0.25 and 0.24 g) was obtained at 500, 1000 and 1500 kg ha−1 doses, respectively. The highest plant height, number of main branches, and number of pod parameters were obtained at a dose of 1500 kg ha−1 in the second production season (36.63 cm, 3.95 and 17.43, respectively). The highest grain yield (889.5 kg ha−1), dry root weight (0.125 g) and number of nodules (50.01) were obtained at a dose of 1000 kg ha−1 in the second production season. It was determined that different sowing methods did not affect grain yield in either production season.